Sobre alguns traços idealistas na "interpretação espiritualista" de Max Weber: da fragmentação estética à crise ética moderna - Roselino, Luis Felipe Martins de Salles (Universidade Federal de São Carlos, 2014)
The main subject of this investigation is concerned with the idealistic influences on Max Weber spiritualistic interpretation. The problem gained as heritage from German idealism, initially referred as an inverted world , since it can be understood as the difficulty that challenges the historic interpretation of practical values, this problem may be also identified inside Max Weber s interpretation of both, ethical and aesthetical phenomena. This investigation is twofold, as the subtitle indicates; the first part shall deal with the aesthetical fragmentation, the emergence of conflictive values in the artistic phenomena. The second part shall deal with the ethical crisis, undertaking this expression in the most literal sense, as a breakdown or a rupture of the ethical world. Both interpretations shall joint together, composing the Weberian diagnosis of an absolute polytheism and of the problem of theodicy. The Weberian theory of values once properly grasped shall finally guide us to draw a conclusion about the relation between spiritualistic and materialistic interpretations, as presented in the guidelines of Max Weber s greatest interests in the economic ethics of the world religions.
Keywords: Weber, Max, 1864-1920; Valores; Politeísmo; Materialismo; Idealismo; Teoria dos valores; Interpretação espiritualista; Teodiceia; Theory of value; Polytheism; Spiritualistic interpretation; Materialism; Idealism; Theodicy; CIENCIAS HUMANAS::FILOSOFIA